Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I try to solve some exercises from Conway "Functional Analysis", and I have some problems with the following: $P,Q,PQ$ are orthogonal projections.

(1) $PQ$ is orthogonal projection iff $PQ=QP$

(2) $\ker(PQ)$=$\ker(P)+\ker(Q)$

I already proved that if $PQ$ is a projection then $PQ=QP$. For the other direction I need to show that $PQ=(PQ)^2$ (because then we know that $PQ$ is idempotent), but I have no idea how to prove it.

For (2) I have no idea.

share|cite|improve this question
For (1), start with $(PQ)^2 = PQPQ$ and use the premise that $PQ=QP$ to simplify. For (2), it depends on whether $PQ,P,Q$ are orthogonal or not. – Christian Clason Nov 28 '12 at 15:06
Yes, PQ, P,Q are all orthogonal – Voyage Nov 28 '12 at 15:09
Then you can use that any vector $v$ can be decomposed as $v=v_1 + v_2$, where (for example) $v_1\in ker P$ and $v_2 \in (ker P)^\bot = ran(P)$. – Christian Clason Nov 28 '12 at 15:12
The first statement is false, even assuming that everything is orthogonal: take $P$ any orthogonal operator, and $Q$ to be the identity. Then $PQ=QP=P$ but $P$ need not be a projection. – Chris Eagle Nov 28 '12 at 15:15
You should edit your question to include this information. – Christian Clason Nov 28 '12 at 15:18
up vote 3 down vote accepted

You are not saying it in the question, but you are assuming that both $P,Q$ are orthogonal projections (i.e. $P^*P=P$, $Q^*Q=Q$).

For (1), if $PQ=QP$, then $(PQ)^2=PQPQ=PPQQ=PQ$, and $(PQ)^*=QP=PQ$.

For (2), you are assuming (again without saying!) that $PQ$ is a projection. First, if $x\in\ker P+\ker Q$, then $x=y+z$ with $Py=0$, $Qz=0$. Then $$ PQx=PQ(y+z)=PQy+PQz=QPy+PQz=0+0=0. $$ So $\ker P+\ker Q\subset\ker PQ$. Conversely, if $x\in\ker PQ$, then $PQx=0$, so $Qx=(I-P)Qx$. Then $x=Qx+(I-Q)x=(I-P)Qx+(I-Q)x$, and $(I-P)Qx\in\ker P$, $(I-Q)x\in\ker Q$. So $\ker PQ\subset\ker P+\ker Q$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.